Systems Biology of RNA Binding Proteins - Yeo, Gene W.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
After transcription in the nucleus, RNA binding proteins (RBPs) recognize cis-regulatory RNA elements within pre-mRNA sequence to form mRNA-protein (mRNP) complexes. Similarly to DNA binding proteins such as transcription factors that regulate gene expression by binding to DNA elements in the promoters of genes, RBPs regulate the fate of target RNAs by interacting with specific sequences or RNA secondary structural features within the transcribed RNA molecule. The set of functional RNA elements recognized by RBPs within target RNAs and which control the temporal, functional and spatial dynamics of the target RNA define a putative “mRNP code”. These cis-regulatory RNA elements can be found in the 5’ and 3’ untranslated regions (UTRs), introns, and exons of all protein-coding genes. RNA elements in 5’ and 3’ UTRs are frequently involved in targeting RNA to specific cellular compartments, affecting 3’ end formation, controlling RNA stability and regulating mRNA translation. RNA elements in introns and exons are known to function as splicing enhancers or silencers during the splicing process from pre-mRNA to mature mRNA. This book provides case studies of RNA binding proteins that regulate aspects of RNA processing that are important for fundamental understanding of diseases and development. Chapters include systems-level perspectives, mechanistic insights into RNA processing and RNA Binding proteins in genetic variation, development and disease. The content focuses on systems biology and genomics of RNA Binding proteins and their relation to human diseases.
Encyclopedia of RNA binding protein expression and domain annotations -- RNA localization and RNA binding proteins that control localization -- Genome-wide approaches to studying alternative polyadenylation events and the RBPs that control them -- RNA binding proteins, PRC complex and long ncRNAs -- Gene and genome regulation by piwi proteins -- Engineering Artificial RBP interactions -- Querying functional polymorphisms by high throughput binding and functional assays -- RNA binding protein networks in EMT/MET -- Therapies against diseases associated with RNA processing defects and RNA binding proteins -- Repeat-disorders and the RNA binding proteins implicated in them -- RNA binding proteins in heart development -- Identification of miRNAs and their targets in C elegans -- Splicing code -- Index.
Keywords: Systems biology; Proteins .; Gene expression; Systems Biology; Protein Science; Gene Expression